Microbiological examination methods of food and water : a laboratory manual - Silva, Neusely da; Gomes, Reneto A. R.; Junqueira, Valeria C. A.; Silveira, Neliane F. A.; Taniwaki, Marta Hiromi
"Illustrated laboratory manual that provides an overview of current standard microbiological culture methods for the examination of food and water, adhered to by renowned international organizations, such as ISO, AOAC, APHA, FDA and FSIS/USDA. The didactic setup and the visualization of procedures in step-by-step schemes allow student and practitioner to quickly perceive and execute the procedure intended. Each chapter provides numerous methods for a certain examination, and also simple alternatives. Intended as a practical companion for researchers, analysts, technicians and teachers, and for laboratory education of (under)graduate students in food engineering and related disciplines"